-10х+7=-х

х-7=-4х

-2х-10=-9х

-10х+8=-х

-х-4=-10х

10(х+4)=7

5(х-10)=4

4(х-8)=9

5(+5)=6

5(х-5)=-9

-9-7х=2х+7

2

Ответы и объяснения

2013-03-01T15:45:05+00:00

1)-10x+x=-7

-9x=-7

9x=7(домножили на -1 обе части)

x=7/9

2)х-7=-4х

x+4x=7

5x=7

x=7/5=1.4

3)-2х-10=-9х

-2x+9x=10

7x=10

x=10/7=1и 3/7

4)-10х+8=-х

-10x+x=-8

-9x=-8

9x=8(обе части на -1)

x=8/9

5)-х-4=-10х

-x+10x=4

-9x=4

x=-4/9

6)10(х+4)=7

10x+40=7

10x=7-40

10x=-34

x=-34/10=-3.4

7)5(х-10)=4

5x-50=4

5x=54

x=54/5=10.8

8)4(х-8)=9

4x-32=9

4x=41

x=41/4=10.25

9)5(+5)=6

Тут вероятно 5(x+5)=6

5x+25=6

5x=-19

x=-19/5=-3.8

10)5(х-5)=-9

5x-25=-9

5x=16

x=16/5=3.2

11)-9-7х=2х+7

-7x-2x=7+9

-9x=16

x=-16/9=-1и  5/9

2013-03-01T15:46:04+00:00

x=10/7

x=7/5

x=10/7

x=8/9

x=4/9

x=-33/10

x=54/5

x=57/4

x=-19/5

x=16/5

x=-16/9